Reiteration Formulae for the Real Interpolation Method Including L or R Limiting Spaces - Leo R. Ya. Doktorski (Journal of Function Spaces)
We consider a real interpolation method defined by means of slowly varying functions. We present some reiteration formulae including so-called L or R limiting interpolation spaces. These spaces arise naturally in reiteration formulae for the limiting cases θ=0 or θ=1. Applications to grand and small Lorentz spaces are given.